A study of bb̄ production in e+e- collisions at √ = 130-207 GeV - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; Anashkin, E; et al. (2009)
Measurements are presented of R b, the ratio of the cross-section to the cross-section in e+e- collisions, and the forward-backward asymmetry A FBb at twelve energy points in the range sqrts=130-207 GeV. These results are found to be consistent with the Standard Model expectations. The measurements are used to set limits on new physics scenarios involving contact interactions. © 2009 Springer-Verlag / Società Italiana di Fisica.